Os ladrilhos da escrita memorial em Infância de Graciliano Ramos - Jesus, Ana Paula Ricci de (Universidade Federal de São Carlos, 2022)
The aim of this work is to present an interpretation of the work Infância by Graciliano Ramos under the memorialist perspective, specifically concerning to a certain aesthetic of the memory in the book. For the composition of this analysis, we seek to highlight the writing of the self of the narrative, both for the recognition of the characteristics of autofiction as a literally genre, and the configuration of a testimonial writing and singular meaning for elaborating childhood’s traumas mediated by violence. To relate these different perceptions, we also develop the hypothesis of impressionism techniques drawing the necessary lines and giving colors and sensations to the author’s memory fragments, in a non-linear portrait, just like fundamental principles of reminiscence. Finally, the last part of the dissertation tries to reveal these elements from excerpts from the book Infância itself.
The tiled narrative of the self in Infância by Graciliano Ramos
Keywords: Graciliano Ramos; Infância; Memória; Impressionismo; Autoficção; Memory; Impressionism; Autofiction; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA